2003
DOI: 10.1080/0892701031000137512
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Brushes for Removal of Fouling from Fouling-release Surfaces, Using a Hydraulic Cleaning Device

Abstract: A portable hydraulic device has been developed for use in optimizing the design of brushes and cleaning units that may be employed to maintain fouling-release coatings. Laboratory tests showed that characteristics of experimental cleaning brushes, including bristle stiffness, density, and angle, significantly affected the shear and normal forces imparted to the surface and thus, to any encrusting organisms. The standoff distance between the cleaning unit and the surface also influenced the forces generated. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…Moreover, comparisons between this study and another of two similar vessels (Davidson et al, 2008), suggest that in-water cleaning is more effective at creating bare space and removing organisms than transit alone. Holm et al (2003) have demonstrated that several factors, including brush position, brush angle, rotation rate, bristle density and bristle stiffness, interact in a complex manner to determine the forces required to remove organisms from submerged surfaces. They also highlighted an important consideration for in-water cleaning of commercial vessels; the forces applied by brushes are generally required to remove organisms with minimal damage or removal of paints.…”
Section: Bio Fo Ul In G An D In -Water Cl Ean In Gmentioning
confidence: 99%
“…Moreover, comparisons between this study and another of two similar vessels (Davidson et al, 2008), suggest that in-water cleaning is more effective at creating bare space and removing organisms than transit alone. Holm et al (2003) have demonstrated that several factors, including brush position, brush angle, rotation rate, bristle density and bristle stiffness, interact in a complex manner to determine the forces required to remove organisms from submerged surfaces. They also highlighted an important consideration for in-water cleaning of commercial vessels; the forces applied by brushes are generally required to remove organisms with minimal damage or removal of paints.…”
Section: Bio Fo Ul In G An D In -Water Cl Ean In Gmentioning
confidence: 99%
“…However, silicone coatings are susceptible to abrasion damage which can compromise their durability. Also, particularly if applied to vessels with periods of inactivity or that do not maintain operating speeds greater than 15 knots, hydrodynamic forces are insuffi cient to completely remove fouling organisms and cleaning may be required to keep the hulls fouling-free and maintain performance (Swain, 1999;Holm et al, 2003). Conventional mechanised in-water cleaning equipment utilises stiff, rotating brushes, and these damage the soft top coats and compromise future performance of silicone foul release systems, requiring the development of modifi ed brushes and in-water cleaning techniques (Holm et al, 2003).…”
Section: Synthesis and Discussionmentioning
confidence: 99%
“…Also, particularly if applied to vessels with periods of inactivity or that do not maintain operating speeds greater than 15 knots, hydrodynamic forces are insuffi cient to completely remove fouling organisms and cleaning may be required to keep the hulls fouling-free and maintain performance (Swain, 1999;Holm et al, 2003). Conventional mechanised in-water cleaning equipment utilises stiff, rotating brushes, and these damage the soft top coats and compromise future performance of silicone foul release systems, requiring the development of modifi ed brushes and in-water cleaning techniques (Holm et al, 2003). The greater durability of fl uorinated coatings may suit their application in some niches that do need regular cleaning, with the reduced strength of biofouling adhesion allowing quicker and easier cleaning than for epoxies, urethanes or other inert coatings.…”
Section: Synthesis and Discussionmentioning
confidence: 99%
“…Likewise, the amount of literature on brushing processes is very limited. Research has been conducted into the behaviour of brushes for surface finishing operations Shia et al, 1989;Heinrich et al, 1991;Stango and Shia, 1997;Fitzpatrick and Paul, 1987), removal of fouling from surfaces (Holm et al, 2003), post-CMP (Chemical Mechanical Planarization) cleaning (Philipossian and Mustapha, 2003;Moumen and Busnaina, 2001), air duct cleaning (e.g., Holopainen and Salonen, 2002), and street sweeping (Wang, 2005;Peel and Parker, 2002;Peel, 2002;Vanegas Useche et al, 2007Abdel Wahab et al, 2007). Relevant details of research into street sweeping and brushing technology are discussed in this section.…”
Section: Related Workmentioning
confidence: 97%